Interdelivery intervals for a vaginal birth after caesarean delivery - Mohd Yusof, Norhayati; Ismail, Hamizah; Nusee, Zalina; Mohd Rus, Razman (IIUM Press, International Islamic University Malaysia, 2017)
The aim of this study was to determine the successful rate of vaginal birth after caesarean (VBAC) in women with inter-delivery interval (IDI) below and above 19 months (≤ 19 months), apart from comparing the maternal morbidity and the fetal outcome between the two groups. This is a cross-sectional study that was conducted in the Obstetrics & Gynaecological Department Hospital Tengku Ampuan Afzan, Kuantan Pahang from June 2013 until June 2015. The sample populations were women who had one previous caesarean section currently pregnant with singleton foetus in cephalic presentation. Those who have had a VBAC and those who were not suitable for VBAC were excluded from the study. The collected data were analyzed using IBM SPSS Statistics 20. Chi-square and Fisher exact tests were employed for categorical variables, and the Independent-samples t- test was used for continuous variables. Multivariate analysis was done using binary logistic regression to evaluate the association of VBAC success with inter-delivery interval and other potential confounding factors. A P value of < 0.05 was considered statistically significant. Of the 590 women, 300 of them were randomly chosen for analysis. Sixty of them were in the group A (IDI≤19 months) while 240 women were in the group B (IDI >19 months). In this study, the shorter the IDI, the higher success rate of VBAC (78.3% versus 55% for group A and group B respectively). There was no difference in terms of maternal morbidities of the two groups. The rates of uterine rupture or dehiscence were also of no significant difference for both groups (0.0% versus 0.4%; p = 0.632). No significant perinatal outcome was also observed. As a conclusion, in our population, the success rate of VBAC for IDI≤19 months were comparable to the IDI>19 months, and with no significant association either with maternal or neonatal morbidity. Therefore, these results may be helpful to obstetricians for counseling and recommending VBAC for women with short inter-delivery interval. Thus the aim of reducing caesarean section rates and its associated morbidity can be achieved.